TINJAUAN YURIDIS TERHADAP LAYANAN KECERDASAN BUATAN (AI) - Farida, Nur; Retno Wulan, Evi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Technology that develops as a tool for people's lives is now increasingly diverse, ranging from the simple to the most sophisticated. One of the results of this sophistication is known as artificial intelligence (AI). The use of AI services that have been comprehensive in all sectors of life and in various forms including AI Chatbot and Generative AI, will have a negative impact on its users if not used responsibly. Until now, the Indonesian government has not issued legal regulations that specifically regulate the use of AI. The purpose of this study is to examine the legal certainty of the accuracy of AI service information and the legal protection of personal data on the use of AI artificial intelligence services. The research method is normative juridical method using a statute approach, and conceptual approach. From the research, it can be concluded that there is a need for regulations that specifically regulate the implementation of AI services in Indonesia.